2012
DOI: 10.5001/omj.2012.06
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Antenatal Patients in Ilorin, Nigeria

Abstract: The prevalence of asymptomatic bacteriuria in Ilorin is high and routine urine culture is advocated for all pregnant women at booking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
26
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 17 publications
11
26
4
Order By: Relevance
“…8 Various studies in India have reported the prevalence ranging from 6% to 22%.2,9,10 Reports from across the world has documented a prevalence of as high as 40-45%. 11,12 As per the present study higher incidence of ASB was seen in the second trimester of pregnancy 8 (57.1%) which was similar to Nath et al and Roy et al 7,13 Yasodhara et al has reported higher incidence of ASB in the first trimester of pregnancy in contrast to our study. 14 Higher incidence in the second trimester of pregnancy could be due the anatomical changes occurring in the uterus, structural and functional changes in the urinary tract like dilatation of ureters favoring stasis of urine leading on to infection.…”
Section: Discussioncontrasting
confidence: 57%
“…8 Various studies in India have reported the prevalence ranging from 6% to 22%.2,9,10 Reports from across the world has documented a prevalence of as high as 40-45%. 11,12 As per the present study higher incidence of ASB was seen in the second trimester of pregnancy 8 (57.1%) which was similar to Nath et al and Roy et al 7,13 Yasodhara et al has reported higher incidence of ASB in the first trimester of pregnancy in contrast to our study. 14 Higher incidence in the second trimester of pregnancy could be due the anatomical changes occurring in the uterus, structural and functional changes in the urinary tract like dilatation of ureters favoring stasis of urine leading on to infection.…”
Section: Discussioncontrasting
confidence: 57%
“…Even though all pregnant women with ASB received antimicrobial treatment, an increased incidence of preterm labour (RR 3.27, 95% CI 1.38-7.72) and neonatal weight below the 10th percentile (RR 3.79, 95% CI 1.80-7.97) was found in women with ASB in the third trimester compared with women without ASB. Unfortunately, the authors do not provide a definition of 'significant' growth or 'positive culture' in the methods [15]. Another study performed in Nigeria showed a 40% prevalence of ASB (50 of 124 women) in pregnant women between 9 and 24 weeks' gestation.…”
Section: Epidemiologymentioning
confidence: 99%
“…A count of less than 10 4 /mL of urine was considered to be not significant. Each significant isolate was identified by colony morphology, gram staining and biochemical reaction according to standard procedures [12,13].…”
Section: Methodsmentioning
confidence: 99%